Transformasi Identitas Dan Peran Publik Muslimah di Era Digital: Perspektif Fenomenologis Terhadap Program Pemberdayaan Melalui Pendidikan Inovatif di Ma Qudsiyyah Putri Kudus - Mohammad Noval Azka; Salmah Fa’atin (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Sekolah Tinggi Agama Islam Mulia Astuti (STAIMAS) Wonogiri, 2026)
Digital transformation has brought significant changes to various aspects of life, including Islamic education, which is required to adapt to technological developments while maintaining Islamic values. In this context, women's empowerment through innovative education becomes essential in shaping Muslim women with intellectual capacity, digital literacy, and the ability to actively participate in the public sphere. This study aims to describe the implementation of innovative education in strengthening the public role of Muslim women in the digital era at MA Qudsiyyah Putri. The study employed a qualitative approach using a phenomenological design. Data were collected through interviews, observations, and documentation involving the principal, vice principal for curriculum affairs, research supervisors, and female students. Data analysis was conducted using a phenomenological approach through the processes of coding, theme development, and interpretation of participants’ lived experiences. The findings indicate that innovative education at MA Qudsiyyah Putri is implemented through the integration of Salaf-based education with research culture and digital literacy. Digital literacy is not merely understood as the ability to use technology but also as a means of accessing and developing knowledge through academic activities. The involvement of female students in research activities contributes to increased self-confidence, strengthened intellectual capacity, and the expansion of Muslim women's public roles. The implementation of innovative education is supported by facilities, mentoring, and institutional networks, although it still faces challenges such as time limitations and research data validation. This study demonstrates that innovative education in Islamic educational institutions plays an important role in shaping adaptive, empowered Muslim women with intellectual authority in the digital era.